Terminal Care Performance of Nurses Caring for COVID‐19 Patients: A Cross‐Sectional Descriptive Study - Juyeon Oh; Dong‐Hee Kim; Yujin Kim (Nursing Open)
ABSTRACT Aims To identify the effects of moral distress and terminal care stress on the terminal care performance of nurses who cared for COVID‐19 patients. Design This study was cross‐sectional descriptive research. Methods Using a convenience sampling method from June to October 2022, nurses who provided terminal care for COVID‐19 patients in a Korean tertiary hospital within the last 6 months from the time of the study were selected as participants. Socio‐demographic and work characteristics of the participants were collected, and COVID‐19 moral distress, terminal care stress and terminal care performance were assessed. A total of 140 self‐report questionnaires were distributed and returned (response rate: 100%). Results In the terminal care performance, it was found that nurses performed relatively well in the physical area, but less well in the emotional and spiritual areas. Moral distress and terminal care stress were both positively correlated with terminal care performance for nurses who cared for COVID‐19 patients. The predictors of terminal care performance were moral distress (β = 0.27, p = 0.003), gender (β = 0.20, p = 0.015) and experience in a dedicated COVID‐19 unit (β = 0.22, p = 0.020). Conclusions The study identified moral distress as the most significant factor influencing terminal care performance among nurses caring for COVID‐19 patients. To enhance terminal care performance, it is crucial to address moral distress and provide clear guidelines and support, especially in the emotional and spiritual care domains. Future research should explore additional factors that may influence terminal care performance in pandemic situations. Patient or Public Contribution No patient or public contribution.